2018
DOI: 10.1029/2017gl076666
|View full text |Cite
|
Sign up to set email alerts
|

Physical Controls on Oxygen Distribution and Denitrification Potential in the North West Arabian Sea

Abstract: At suboxic oxygen concentrations, key biogeochemical cycles change and denitrification becomes the dominant remineralization pathway. Earth system models predict oxygen loss across most ocean basins in the next century; oxygen minimum zones near suboxia may become suboxic and therefore denitrifying. Using an ocean glider survey and historical data, we show oxygen loss in the Gulf of Oman (from 6-12 to <2 μmol kg À1 ) not represented in climatologies. Because of the nonlinearity between denitrification and oxyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 46 publications
3
63
0
Order By: Relevance
“…For example, the depth of the oxycline in both the AS and BoB is strongly related to sea surface height variations driven by mesoscale eddies (Prakash et al, ). Glider observations in the northwest AS demonstrate the role of eddies in transporting oxygen (Queste et al, ). There is little seasonal variability in the frequency of eddies found in the BoB, but there are large, interannual changes in the eddy number (Chen et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…For example, the depth of the oxycline in both the AS and BoB is strongly related to sea surface height variations driven by mesoscale eddies (Prakash et al, ). Glider observations in the northwest AS demonstrate the role of eddies in transporting oxygen (Queste et al, ). There is little seasonal variability in the frequency of eddies found in the BoB, but there are large, interannual changes in the eddy number (Chen et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Considering the mean ventilation time of OMZ to be 12 years (Sarma, ), the rate of oxygen input through PGW is estimated to be 0.003 to 0.005 μmol/L/day. Queste et al () suggested that PGW may not bring significant amount of DO to the BoB as it passes through intensely DO‐depleted OMZ of the AS before entering to BoB. Nevertheless, the supply of oxygen through horizontal advection of PGW is an order of magnitude less than that from ACEs (0.07 ± 0.02 μmol/l/d) and bacterial respiration rates (0.02 ± 0.004 μmol/l/d), suggesting that ventilation of oxygen through ACEs is very important in the maintenance of OMZ.…”
Section: Resultsmentioning
confidence: 99%
“…Settings similar to the Arabian Sea, with ≤ 4.5 μmol kg -1 O 2 , occur in the East Pacific and those settings in total occupy an area of 8.45 to 15 × 10 12 m 2 (Karstensen et al, 2008;Hattori, 1983;Paulmier & Ruiz-Pino, 2009), or a volume of 0.46 × 10 15 m 3 with 1.148 × 10 12 m 2 in contact with the sediment (Helly & Levin, 2004). OMZs are expanding in size and in volume (Queste et al, 2018;Stramma et al, 2010), and anammox bacteria play a key role in these settings, particularly because they tolerate higher oxygen concentrations than denitrifiers (Dalsgaard et al, 2014). The labile organic matter added to the sinking carbon can fuel heterotrophic processes, further exacerbating oxygen depletion, and nitrogen loss by denitrification.…”
Section: Quantifying the Biological Pump And Remineralization Ratesmentioning
confidence: 99%